Dimensionally controlled water-dispersible amplifying fluorescent polymer nanoparticles for selective detection of charge-neutral analytes. Issue 48 (29th November 2017) - Shin, Suyong; Lim, Jeewoo; Gu, Ming-Long; Yu, Chin-Yang; Hong, Mooncheol; Char, Kookheon; Choi, Tae-Lim
Abstract : Fluorescent nanoparticles composed of poly( p -phenylenevinylene) block copolymers were prepared by the facile one-step process and exhibited discriminative detection of neutral explosives against charged molecules. Abstract : Controlled nanoscale assemblies of conjugated polymers are of considerable interest due to their potential for optimised energy transport properties. Recent progress in the development of conjugated block copolymers (BCPs) and their self-assembly have yielded controlled nanostructures unattainable using conventional synthesis via step-growth polymerisation. The self-assembly procedures, however, often require tedious and complicated manipulations during and/or after the polymerisation, and simple, efficient methods for the preparation of such conjugated block copolymer nanostructures have remained a formidable challenge. Herein, we report the preparation of fluorescent poly( p -phenylenevinylene) (PPV) BCP nanostructures in a dimensionally controlled manner through a simple, one-shot ring-opening metathesis polymerisation wherein the BCP formation and self-assembly occur simultaneously. The driving force of the in situ self-assembly is ascribed to the insolubility and the strong interchain π–π interactions of the core-forming block, making it possible to use a fluorescent block with low crystallinity. The introduction of an appropriate non-conjugated solubilizing block renders the nanostructures water-dispersible, and they exhibit a morphology-dependent fluorescence quenching response in the presence of trace amounts of nitroaromatics, including 2, 4, 6-trinitrotoluene (TNT). The quenching response shows remarkable discrimination against paraquat, a widely used electron-acceptor and a strong quencher, in favor of neutral analytes.